Shopping malls and commercial strips: an examination of factors affecting shoppers behavior in Kuwait - Bagnied, Mohsen (2016)
Traditional malls are as popular as the modern malls in Kuwait. In this study, the authors examine the shopping orientation and patronage of mall shoppers in Kuwait. A sample of about 2,500 consumers was surveyed and the survey was focused on the factors that influence shopping behaviour. The result of the study shows that females and younger respondents tend to favor modern shopping malls over traditional malls. Mall preference was based on the availability of different shops followed by nice environment. Advertising was found to be the major influence in selecting products and services, while the importance of family, peers, and friends came second followed by price. In Kuwait, most people shop for quality and value rather than price.